Iron oxide - clay composite vectors on long-distance transport of arsenic and toxic metals in mining-affected areas. (April 2018) - Gomez-Gonzalez, Miguel A.; Villalobos, Mario; Marco, Jose Francisco; Garcia-Guinea, Javier; Bolea, Eduardo; Laborda, Francisco; Garrido, Fernando
Abstract: Mine wastes from abandoned exploitations are sources of high concentrations of hazardous metal(oid)s. Although these contaminants can be attenuated by sorbing to secondary minerals, in this work we identified a mechanism for long-distance dispersion of arsenic and metals through their association to mobile colloids. We characterize the colloids and their sorbed contaminants using spectrometric and physicochemical fractionation techniques. Mechanical action through erosion may release and transport high concentrations of colloid-associated metal(oid)s towards nearby stream waters, promoting their dispersion from the contamination source. Poorly crystalline ferrihydrite acts as the principal As-sorbing mineral, but in this study we find that this nanomineral does not mobilize As independently, rather, it is transported as surface coatings bound to mineral particles, perhaps through electrostatic biding interactions due to opposing surface charges at acidic to circumneutral pH values. This association is very stable and effective in carrying along metal(oid)s in concentrations above regulatory levels. The unlimited source of toxic elements in mine residues causes ongoing, decades-long mobilization of toxic elements into stream waters. The ferrihydrite-clay colloidal composites and their high mobility limit the attenuating role that iron oxides alone show through adsorption of metal(oid)s and their immobilization in situ. This may have important implications for the potential bioavailability of these contaminants, as well as for the use of this water for human consumption. Graphical abstract: Image 1 Highlights: Long-distance dispersion of arsenic through mobile colloids is demonstrated. Ferrihydrite found as thin coatings on clay minerals acts as arsenic sorbing phase. This association carries other metals in concentrations above regulatory levels. This association limits the role of iron oxides to attenuate arsenic pollution. Abstract : Capsule: This study indicates that nano-ferrihydrite may mobilize arsenic as mineral coatings on the surface of clay minerals. This demonstrates the role of iron coatings as arsenic scavengers and potential vector.